Glycogen Synthase Kinase 3 Inactivation Compensates for the Lack of CD28 in the Priming of CD8+ Cytotoxic T-Cells: Implications for anti-PD-1 Immunotherapy - Taylor, Alison; Rudd, Christopher E. (Frontiers in Immunology, 2017)
The rescue of exhausted CD8+ cytolytic T-cells (CTLs) by anti-PD-1 blockade has been found to require CD28 expression. At the same time, we have shown that the inactivation of the serine/threonine kinase GSK-3α/β with small interfering RNAs (siRNAs) and small molecule inhibitors (SMIs) specifically down-regulate PD-1 expression for enhanced CD8+ CTL function and clearance of tumours and viral infections. Despite this, it has been unclear whether the GSK-3α/β pathway accounts for CD28 co-stimulation of CD8+ CTL function. In this paper, we show that inactivation of GSK-3α/β through siRNA or by SMIs during priming can substitute CD28 stimulation in the potentiation of cytotoxic CD8+ CTL function. This increased response was observed in the blockade of CD28 co-receptor by CTLA-4-IgG in OT-1 T-cells responding to OVA peptide as presented by the lymphoma cell line EL4. The effect was seen using several GSK-3 SMIs, and was accompanied by an increase in Lamp-1 and GZMB expression. Conversely, CD28 crosslinking obviated the need for GSK-3α/β inhibition in its enhancement of CTL function. Our findings support a model where GSK-3 is the central co-signal for CD28 priming of CD8+ CTLs in anti-PD-1 immunotherapy. □